2011
DOI: 10.1159/000331712
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Phospholamban Phosphorylation and S-Nitrosylation in the Negative Lusitropism Induced by 17β-estradiol in the Male Rat Heart

Abstract: Background/Aims: 17β-estradiol (17βE2) plays an important cardiovascular role by activating estrogen receptors (ER) α and ERβ. Previous studies demonstrated that the novel estrogen G protein-coupled receptor (GPR30/GPER) mediates estrogen action in different tissues. We have recently shown in the rat heart that 17βE2 elicits negative inotropism through ERα, ERβ and GPR30, by triggering activation of ERK1/2, phosphatidylinositol 3-kinase (PI3K), protein kinase A (PKA) and endothelial Nitric Oxide synthase (eNOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
2
12
0
2
Order By: Relevance
“…Recently, Chen and coworkers (14) showed that endogenous H 2 S contributes to inactivate SERCA2a pump, and thus SR Ca 2ϩ uptake through PLN dephosphorylation. Our previous studies have demonstrated an important role of PLN in the lusitropic action of several cardioactive substances, such as catestatin and 17-␤-estradiol through both phosphorylation and S-nytrosylation mechanism (5,6,19). Together with the literature data, we suggested PLN S-sulfhydration as an alternative mechanism for SERCA2a regulation, with putative consequences on the H 2 S-dependent negative inotropic and lusitropic actions.…”
Section: Protein S-sulfhydrationsupporting
confidence: 66%
“…Recently, Chen and coworkers (14) showed that endogenous H 2 S contributes to inactivate SERCA2a pump, and thus SR Ca 2ϩ uptake through PLN dephosphorylation. Our previous studies have demonstrated an important role of PLN in the lusitropic action of several cardioactive substances, such as catestatin and 17-␤-estradiol through both phosphorylation and S-nytrosylation mechanism (5,6,19). Together with the literature data, we suggested PLN S-sulfhydration as an alternative mechanism for SERCA2a regulation, with putative consequences on the H 2 S-dependent negative inotropic and lusitropic actions.…”
Section: Protein S-sulfhydrationsupporting
confidence: 66%
“…Thus, PLN levels and activity may also be under the control of myostatin or a myostatin-regulated factor, as with SERCA2a. Estradiol inhibits, rather than stimulates, PLN activation and does not appear to regulate PLN expression (74). Gonadal steroids may therefore influence myostatin sensitivity, but are likely not directly responsible for the noted sexual dimorphism.…”
Section: Discussionmentioning
confidence: 95%
“…Phosphorylation of Akt at Thr308 and Ser473 was also prevented by the MEK inhibitor PD98059 (50 µM) [19] (Fig. 2D) and the ERK1/2 inhibitor FR180204 (10 µM) [20,21] (Fig.…”
Section: Resultsmentioning
confidence: 99%